Students’ Perception of Applying Teacher-in-Role during English Learning Process: A Descriptive Study of Middle School Students - Firdaus, Fatimah; Melani, Melyann (Journal of Education, Language Innovation, and Applied Linguistics, 2024)
Teacher-in-Role becomes one of the effective methods in the teaching and learning process which indicates the teacher also contributes to playing a role in the classroom to engage the students to take a part a role. This study aimed to describe students’ perception of applying Teacher-in-Role which reflected the purpose of Teacher-in-Role. There were some purposes namely, stabilize the students’ attention, trigger affective and cognitive responses, provide and collect information, try to speak and respond, face challenges or issues and try to handle them, and communicate patterns between teacher and students while Teacher-in-Role. This study was a descriptive study with interviews through focus group discussion as the instrument of this study. There were 10 students in one of the high schools in Padang who participated in this study. The result of this study was a positive perception of students who applied Teacher-in-Role in the classroom. It increased students’ enthusiasm for learning and built a natural atmosphere while they played a role. The students are encouraged trying to take a role due to the unique characters that should be taken. The teachers also became part of them to play the role and also provide them the precise information. However, there was a student to showed the opposite which Teacher-in-Role was ordinary because the students face issues such as nervousness, limited vocabulary, less confidence, and tend to be passive in the classroom. Overall, the students illustrated the positive perception of applying Teacher-in-Role in teaching and learning. Keywords: Descriptive study; Learning; Perception; and Teacher-in-Role.